In vitro antiproliferative, anti-inflammatory effects and molecular docking studies of natural compounds isolated from Sarcocephalus pobeguinii (Hua ex Pobég) - Mfotie Njoya, Emmanuel; Ndemangou, Brigitte; Akinyelu, Jude; Munvera, Aristide M.; Chukwuma, Chika. I.; Mkounga, Pierre; Mashele, Samson S.; Makhafola, Tshepiso J.; McGaw, Lyndy J. (Frontiers in Pharmacology, 2023)
Background: Sarcocephalus pobeguinii (Hua ex Pobég) is used in folk medicine to treat oxidative-stress related diseases, thereby warranting the investigation of its anticancer and anti-inflammatory properties. In our previous study, the leaf extract of S. pobeguinii induced significant cytotoxic effect against several cancerous cells with high selectivity indexes towards non-cancerous cells. Aim: The current study aims to isolate natural compounds from S. pobeguinii, and to evaluate their cytotoxicity, selectivity and anti-inflammatory effects as well as searching for potential target proteins of bioactive compounds. Methods: Natural compounds were isolated from leaf, fruit and bark extracts of S. pobeguinii and their chemical structures were elucidated using appropriate spectroscopic methods. The antiproliferative effect of isolated compounds was determined on four human cancerous cells (MCF-7, HepG2, Caco-2 and A549 cells) and non-cancerous Vero cells. Additionally, the anti-inflammatory activity of these compounds was determined by evaluating the nitric oxide (NO) production inhibitory potential and the 15-lipoxygenase (15-LOX) inhibitory activity. Furthermore, molecular docking studies were carried out on six putative target proteins found in common signaling pathways of inflammation and cancer. Results: Hederagenin (2), quinovic acid 3-O-[α-D-quinovopyranoside] (6) and quinovic acid 3-O-[β-D-quinovopyranoside] (9) exhibited significant cytotoxic effect against all cancerous cells, and they induced apoptosis in MCF-7 cells by increasing caspase-3/-7 activity. (6) showed the highest efficacy against all cancerous cells with poor selectivity (except for A549 cells) towards non-cancerous Vero cells; while (2) showed the highest selectivity warranting its potential safety as a chemotherapeutic agent. Moreover, (6) and (9) significantly inhibited NO production in LPS-stimulated RAW 264.7 cells which could mainly be attributed to their high cytotoxic effect. Besides, the mixture nauclealatifoline G and naucleofficine D (1), hederagenin (2) and chletric acid (3) were active against 15-LOX as compared to quercetin. Docking results showed that JAK2 and COX-2, with the highest binding scores, are the potential molecular targets involved in the antiproliferative and anti-inflammatory effects of bioactive compounds. Conclusion: Overall, hederagenin (2), which selectively killed cancer cells with additional anti-inflammatory effect, is the most prominent lead compound which may be further investigated as a drug candidate to tackle cancer progression.